INFLECTION OF CADA AND NUMBER FEATURE VALUATION IN BP - Pereira, Bruna Karla (Estudos Linguísticos e Literários, 2019)
This research investigates nominal concord in structures of non-standard Brazilian Portuguese (BP) where cada is inflected with the plural morpheme -s while the phrases following it may not bear any plural marking. In order to account for this, I will consider that cardinals and silent nouns work as a boundary dividing the DP into two domains such that phrases to their left are marked with the plural morpheme while phrases to their right are unmarked, a pattern found across languages. Additionally, I will argue that DPs with cadas have a silent noun SET and that this silent noun conveys a set reading as well as valued plural features. In this case, cada is interpreted as either ‘such’ or ‘every’ rather than ‘each’ and is followed by a noun or a cardinal ≥ 2 (plus a noun). Accordingly, because cadas precedes SET, it is marked with -s. This plural silent noun is followed by a preposition, which allows its embedded NP to be singular.